PERAN PASANG RI KAJANG DALAM KEBUDAYAAN MASYARAKAT KAJANG, KABUPATEN BULUKUMBA (Studi Etnografi) - -, Asyrafunnisa; Abeng, Andi Tenri (Jurnal Ilmiah Ecosystem, 2019)
This research aims to see the role of Pasang Ri Kajang which is a cultural heritage from ancestors of Kajang tribe society in Bulukumba district, South Sulawesi. This research is expected to be able to provide a substantial contribution in the preservation of local cultural products which are increasingly squeezed by the flow of globalization. In this research used ethnographic method which is regard to the social sciences. This research used library and field research in the form of interview technique. The library research is directed to find the supporting theories about the role of Pasang Ri Kajang. Field research carried out the interview techniques with several informants who were considered representative to provide an overview of all cases that related to the Pasang Ri Kajang culture. The result of data from library and field research used descriptive qualitative techniques to produce conclusions.